Monopoly regulation through cost-based revenue caps employing a base year approach - Gerrit Gräper; Fabian Mankat (Philipps-University Marburg, School of Business and Economics, 2024)
This paper studies the pricing incentives of a monopolist constrained by a revenue cap endogenously determined by her costs in a so-called base year. Such regulation is employed, among others, to govern electricity distribution operators in Germany. We show that the revenue cap may incentivize excessive supply in the base year to reap profits in the non-base years. A connected set of price caps exists so that a hybrid regulation consisting of any element in this set and the cost-based revenue cap unambiguously improves welfare and, under some conditions, even leads to the socially optimal outcome.
Keywords: D21; D42; L12; L51; L94; 330; regulation; monopoly; electricity distribution